What shapes stellar metallicity gradients of massive galaxies at large radii?. Issue Volume 11:Issue S321(2015) (21st March 2017) - Hirschmann, Michaela
Abstract: We investigate the differential impact of physical mechanisms, mergers and internal energetic phenomena, on the evolution of stellar metallicity gradients in massive, present-day galaxies employing sets of high-resolution, cosmological zoom simulations. We demonstrate that negative metallicity gradients at large radii (>2Reff) originate from the accretion of metal-poor stellar systems. At larger radii, galaxies become typically more dominated by stars accreted from satellite galaxies in major and minor mergers. However, only strong galactic, stellar-driven winds can sufficiently reduce the metallicity content of the accreted stars to realistically steepen the outer metallicity gradients in agreement with observations. In contrast, the gradients of the models without winds are inconsistent with observations. Moreover, we discuss the impact of additional AGN feedback. This analysis greatly highlights the importance of both energetic processes and merger events for stellar population properties of massive galaxies at large radii. Our results are expected to significantly contribute to the interpretation of current and up-coming IFU surveys (e.g. MaNGA, CALIFA).